Exposition of semiconducting and ferromagnetic properties of pulsed-laser-deposited thin films of LaFe1-xNixO3 (x=0.3, 0.4, and 0.5) - SHVETS, IGOR; ARORA, SUNIL KUMAR (American Institute of Physics, 2005)
We have explored the possibility of ferromagnetic semiconducting property in the epitaxial thin films of LaFe1?xNixO3 x=0.3, 0.4, and 0.5 grown on 001 oriented LaAlO3 substrate. We observe that substitution of Ni in the series leads to the increase in conductivity of the samples with conduction being controlled by the disorder-induced localization of charge carriers. All these samples show ferromagnetic behavior at room temperature while their magnetization decreases with increase in Ni concentration in the composition. The results have been explained on the basis of the close interplay between the electrical and magnetic properties.
PUBLISHED
Keywords: Surface Physics; thin films